The role of cluster formation and metastable liquid-liquid phase separation in protein crystallization - Zhang, F; Roosen-Runge, F; Sauter, A; Roth, R; Skoda, M; Jacobs, R; Sztucki, M; Schreiber, F (2012)
We discuss the phase behavior and in particular crystallization of a model globular protein (beta-lactoglobulin) in solution in the presence of multivalent electrolytes. It has been shown previously that negatively charged globular proteins at neutral pH in the presence of multivalent counterions undergo a "re-entrant condensation (RC)" phase behavior (Zhang et al., Phys. Rev. Lett., 2008, 101, 148101), i.e. a phase-separated regime occurs in between two critical salt concentrations, c* < c**, giving a metastable liquid-liquid phase separation (LLPS). Crystallization from the condensed regime has been observed to follow different mechanisms. Near c*, crystals grow following a classic nucleation and growth mechanism; near c**, the crystallization follows a two-step crystallization mechanism, i.e, crystal growth follows a metastable LLPS. In this paper, we focus on the two-step crystal growth near c**. SAXS measurements indicate that proteins form clusters in this regime and the cluster size increases approaching c**. Upon lowering the temperature, in situ SAXS studies indicate that the clusters can directly form both a dense liquid phase and protein crystals. During the crystal growth, the metastable dense liquid phase is dissolved. Based on our observations, we discuss a nucleation mechanism starting from clusters in the dilute phase from a metastable LLPS. These protein clusters behave as the building blocks for nucleation, while the dense phase acts as a reservoir ensuring constant protein concentration in the dilute phase during crystal growth. © The Royal Society of Chemistry 2012.